Density functional investigation of metal−metal interactions in mixed-valence d2d3 (Cr, Mo, W) and d3d4 (Mn, Tc, Re) face-shared [M2Cl9]2- systems - Cavigliasso, Germán; Comba, Peter; Stranger, Robert (Inorganic chemistry, 2004)
The molecular and electronic structures of mixed-valence face-shared (Cr, Mo, W) d2d3 and (Mn, Tc, Re) d3d4 [M2Cl9]2- dimers have been calculated by density functional methods in order to investigate metal−metal bonding in this series. The electronic structures of these systems have been analyzed using potential energy curves for the broken-symmetry and other spin states arising from the d2d3 and d3d4 coupling modes. In (d2d3) [Mo2Cl9]2- and [W2Cl9]2-, the global minimum has been found to be a spin-doublet state characterized by delocalization of the metal-based electrons in a multiple metal−metal bond (with a formal bond order of 2.5). In contrast, weak coupling between the metal centers and electron localization are favored in (d2d3) [Cr2Cl9]2-, the global minimum for this species being a ferromagnetic S = 5/2 state with a relatively long Cr−Cr separation. The (d3d4) [Re2Cl9]2- system also exhibits a global minimum corresponding to a metal−metal bonded spin-doublet state with a formal bond order of 2.5, reflecting the electron−hole equivalence between d2d3 and d3d4 configurations. Double minima behavior is predicted for (d3d4) [Tc2Cl9]2- and [Mn2Cl9]2- due to two energetically close low-lying states (these being S = 3/2 and S = 5/2 states for the former, and S = 5/2 and S = 7/2 states for the latter). A comparison of computational results for the d2d2, d2d3, and d3d3 [W2Cl9]z- series and the d3d3, d3d4, and d4d4 [Re2Cl9]z- series indicates that the observed trends in metal−metal distances can only be rationalized if changes in both the strength of σ bonding and metal−metal bond order are taken into consideration. These two factors act conjointly in the W series but in opposition to one another in the Re series. In the case of the [Cr2Cl9]z- and [Mn2Cl9]z- dimers, the metal−metal bond lengths are significantly shorter for mixed-valence (d2d3 or d3d4) than d3d3 systems. This result is consistent with the fact that some degree of metal−metal bonding exists in the former (due to partial delocalization of a single σ electron) but not in the latter (where all metal-based electrons are completely localized).